2001
DOI: 10.1142/s0129183101001912
|View full text |Cite
|
Sign up to set email alerts
|

Extended Ensemble Monte Carlo

Abstract: Extended Ensemble Monte Carlo" is a generic term that indicates a set of algorithms which are now popular in a variety of fields in physics and statistical information processing. Exchange Monte Carlo (Metropolis-Coupled Chain, Parallel Tempering), Simulated Tempering (Expanded Ensemble Monte Carlo), and Multicanonical Monte Carlo (Adaptive Umbrella Sampling) are typical members of this family. Here we give a cross-disciplinary survey of these algorithms with special emphasis on the great flexibility of the un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
175
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(176 citation statements)
references
References 110 publications
(326 reference statements)
1
175
0
Order By: Relevance
“…[6][7][8] A recent review of these methods can be found in the literature. 9 In parallel tempering, several independent replicas of a system are simulated simultaneously. Each replica ͑or simulation box͒ can experience different thermodynamic-state conditions ͑e.g., temperature, pressure, or chemical potential͒.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] A recent review of these methods can be found in the literature. 9 In parallel tempering, several independent replicas of a system are simulated simultaneously. Each replica ͑or simulation box͒ can experience different thermodynamic-state conditions ͑e.g., temperature, pressure, or chemical potential͒.…”
Section: Introductionmentioning
confidence: 99%
“…Improved numerical ergodicity is usually achieved compared to direct Monte Carlo or molecular dynamics simulations by allowing the system to circumvent barriers between metastable basins or even to cross them when, for instance, the external parameter is associated with inverse temperature and takes small values. Because of its popularity and versatility, the expanded ensemble method has been the subject of numerous studies [15][16][17][18][19][20][21] over recent years. To evaluate the thermodynamic expectations, several estimators have been proposed, namely, the (standard) binning estimator, 6 a standard reweighting estimator 21 , a self-consistent reweighting estimator 17 called simulated tempering weighted histogram analysis method (STWHAM), a histogram reweighting estimator 22 called corrected z-averaged restraints (CZAR) and an adiabatic reweighting (AR) estimator.…”
Section: -4mentioning
confidence: 99%
“…We refer the reader to Iba (2001) for the details and to Goswami & Liu (2006) (unpublished technical report) for an alternative approach.…”
Section: Exchange Perform the Delayed Rejection Exchange Movementioning
confidence: 99%